Simple peak detection control algorithm of distribution static compensator for power quality improvement. Issue 7 (1st July 2014) - Singh, Bhim; Arya, Sabha Raj; Jain, Chinmay
Abstract : This study deals with the control of a three‐phase, four‐wire distribution static compensator (DSTATCOM) based on the peak detection of load currents for power quality improvement under linear/non‐linear loads. This control algorithm is simple and easy in real time implementation. In this control algorithm, an extraction of active and reactive power components of load currents is based on a low‐pass filter and the voltage unit vector in time domain. It is based on the mathematical formulations for fast and accurate estimation of reference supply currents. A four‐wire DSTATCOM is modelled and implemented for the compensation of linear and non‐linear loads using a digital signal processor. Performance of DSTATCOM is found quite satisfactory under balanced and unbalanced loads in three‐phase, four‐wire distribution system.